Market integration in the crustaceans market: Evidence from Germany. (January 2018) - Ankamah-Yeboah, Isaac; Bronnmann, Julia
Abstract: In this paper the price dynamics and the degree of market integration in the German crustaceans market is examined using cointegration methods. The study focuses on wild caught cold water shrimp, farmed warm water shrimp as well as lobster and derives implications for the fisheries sector. In the analysis, both the import market and the retail market price reactions are distinguished. Therefore, it is evaluated how price changes affect competing commodities within and between the value chain of a given crustaceans commodity. Evidence of partial market integration is found for all species under study at the import level while at the retail level; there is weak evidence of perfect market integration. At the import-retail level linkages, shrimp markets are partially integrated, while the lobster market is fully integrated. Consequently, it can be concluded that the species under consideration are substitutes. Price determination processes for the shrimp markets vary with the level of the value chain. The results imply that the wild and farmed crustaceans markets are interacting through substitution effects. Hence, the markets have the capability to shield volatile and rising prices that would emanate from supply shocks. Overexploited wild caught species would have the potential to recover and the competing farmed species could expand to at least insure against rising prices due to supply shortage. Thus, alternative fisheries management and development strategies should consider competing species, at least from an economic perspective.